Know Thyself: NK-Cell Inhibitory Receptors Prompt Self-Tolerance, Education, and Viral Control - Nash, William T.; Teoh, Jeffrey; Wei, Hairong; Gamache, Awndre; Brown, Michael G. (Frontiers in Immunology, 2014)
Natural killer cells (NK) provide essential protection against viral infections. One of the defining features of this lymphocyte population is the expression of a wide array of variable cell surface stimulatory and inhibitory NK receptors (sNKR and iNKR respectively). The iNKR are particularly important in terms of NK cell education. As receptors specific for MHC class I (MHC I) molecules, they are responsible for self-tolerance and adjusting NK cell reactivity based the expression level of self-MHC I. The end result of this education is two-fold: 1) inhibitory signaling tunes the functional capacity of the NK cell, endowing greater potency with greater education, and 2) education on self allows the NK cell to detect aberrations in MHC I expression, a common occurrence during many viral infections. Many studies have indicated an important role for iNKR and MHC I in disease, making these receptors attractive targets for manipulating NK cell reactivity in the clinic. A greater understanding of iNKR and their ability to regulate NK cells will provide a basis for future attempts at translating their potential utility into benefits for human health.